A novel fluorescent indicator displacement assay for sensing the anticancer drug gefitinib. Issue 3 (4th March 2017) - Xi, Yun-Yun; Tang, Qing; Huang, Ying; Tao, Zhu; Xue, Sai-Feng; Zhou, Qingdi; Wei, Gang
Abstract: Fluorescent indicator displacement assays have become popular for converting synthetic receptors into optical sensors. We have now shown that a 1:2 host–guest complex between cucurbit[8]uril (Q[8]) and proflavine (PF) can be used as a fluorescent indicator for sensing the anticancer drug gefitinib. The 2PF@Q[8] complex can be used to detect gefitinib with high selectivity using fluorescence spectrometry with a detection limit of 6.63 × 10 −8 mol −L . The proposed sensing mechanism was investigated using 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR), isothermal titration calorimetry and electrospray ionisation mass spectrometry. The 2PF@Q[8] complex was shown to be suitable for imaging gefitinib in prostate cancer (PC3) cells, which may help to elucidate relevant biological processes at the molecular level. We have developed a novel F-IDA to detect the anticancer drug GEF with high selectivity. The new indicator has excellent selectivity and a low detection limit for GEF. We have also demonstrated that the F-IDA can be used for the practical determination of drugs in living cells. Abstract :